The functional and spatial structure of the investment management industry - Clark, G (Elsevier, 2000)
Most pension funds use an extensive array of service providers to administer and manage their financial assets. In this paper, I sketch a 'map' of the functional structure of service provision and the apparent spatial configuration of those elements. Theoretically, the paper could be thought inspired by Richardson, Coase and Williamson, but goes on to consider three substantive issues particular to pension fund management: uncertainty, trustees' fiduciary duty, and managing within cost constraints. While it is apparent that service providers are allocated assets to manage on the basis of their relatives costs and performance, it is also argued that the pattern of service provision in the industry reflects an on-going and unresolved tension between the economics of distrust (implying short-term contracts) and the virtues of commitment (implying long-term relationships). As part of this argument, I consider the role and responsibilities of consultants and advisers to pension fund trustees. Having established four basic models which describe the principle ways of managing the investment process, the paper then deals with the spatial and network related implications of these models. The paper draws upon recent research on pension fund investment in the US, Canada, the UK, and Australia reported in previous papers.